2015
DOI: 10.19030/jabr.v31i5.9412
|View full text |Cite
|
Sign up to set email alerts
|

Motives Behind The Integration Of CSR Into Business Strategy: A Comparative Study In French SMEs

Abstract: <p>Corporate social responsibility (CSR) in the context of small and medium enterprises (SMEs) has become an important and substantial area of study for quite a few years. In this literature, while so much research has shed light on what makes SMEs integrate CSR into their business strategy, the existing results regarding their economic, social, and environmental motives are contradictory. In this article, we aim at making a contribution by conducting an integrative study. More specifically, we compare t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Cantele and Zardini [107]; Dubruc et al [108]; Tok et al [109]; Allet [110]; Carrigan [111]; Corazza [112]; Warren [113]; Goddard et al [114]; Graafland [115]; North [116]; Chang [117]; Panwar et al [118]; Vo et al [119]; Doukas et al [120]; Etoundi Eloundou [121]; Jenkins and Karanikola [122]; Ayuso et al [123]; Ciasullo and Troisi [124]; Musa et al [125]; Torugsa et al [126]; Battisti and Perry [127]; Gliedt and Parker [128]; Gallucci et al [129]; Vancheswaran and Gautam [130]; Redmond et al [131]; Shetty et al [132]; Burke and Gaughran [133], among others.…”
Section: Sustainable Development Management and Environmental Awarementioning
confidence: 99%
“…Cantele and Zardini [107]; Dubruc et al [108]; Tok et al [109]; Allet [110]; Carrigan [111]; Corazza [112]; Warren [113]; Goddard et al [114]; Graafland [115]; North [116]; Chang [117]; Panwar et al [118]; Vo et al [119]; Doukas et al [120]; Etoundi Eloundou [121]; Jenkins and Karanikola [122]; Ayuso et al [123]; Ciasullo and Troisi [124]; Musa et al [125]; Torugsa et al [126]; Battisti and Perry [127]; Gliedt and Parker [128]; Gallucci et al [129]; Vancheswaran and Gautam [130]; Redmond et al [131]; Shetty et al [132]; Burke and Gaughran [133], among others.…”
Section: Sustainable Development Management and Environmental Awarementioning
confidence: 99%
“…In France, research (Vo, Delchet-Cochet, Akeb, 2015) revealed that the economic motive has the highest level of influence in encouraging French SMEs to integrate CSR into their business strategy, followed by the social motive. Only a proactive environmental motive plays a role in environmental protection measures, indicating the extent to which a company is transforming its business and environmental activities (the practice of proactive environmental protection can potentially lead to a competitive advantage through the development of green products).…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…However, the environmental aspect can be classified into two levels: reactive and proactive (Vo, Delchet-Coche, and Akeb, 2015). The proactive level refers to innovation, eco-efficiency, pollution prevention and environmental leadership in order to minimize the ecological impact on the environment through the adoption of environmental management systems that seek to transform the development of operational activities getting involved, beyond the regulatory plans.…”
Section: Environmental Dimensionmentioning
confidence: 99%
“…However, Kirk (1995) states that responsible social behavior can give a hotel firm a commercial advantage with a positive effect on its presentation. In addition, Kabir (2011) states that the image of the hotel is strategic and can help survive competitive conditions, while (García-Rodríguez and Armas-Cruz, 2007) point out that this relationship depends on the local context (Melo, Moura-Leite, and Padgett, 2012) On the other hand, the social role has the workplace and the community as two focus points in the creation of social cohesion and equity, where aspects such as health, safety and general welfare of employees are recognized through the offer of training and development opportunities, social advances in the community, among others (Vo, Delchet-Coche, and Akeb, 2015). According to Porter and Kramer (2006), companies can influence various social factors, such as the local education system, the adequacy of the public health system, availability of accommodation, discrimination, etc.…”
Section: Social Dimensionmentioning
confidence: 99%